COMPARISON OF SERUM ALANINTRANSFERASE, TRANSFERRIN AND LACTOGLOBULIN LEVELS IN CHRONIC HBV INFECTION AMONG HBeAg POSITIVE AND NEGATIVE CASES - Alaaddin PAHSA; Alaaddin PAHSA; Aziz HACIBEKTAŞOĞLU; Oğuz TUNCER YILMAZ; Ş. Volkan ÖZGÜVEN; Altuğ BARUT (Turkish Journal of Gastroenterology, 2020)
-